Ionic Components of Electric Current at Rat Corneal Wounds - Vieira, Ana Carolina [UNIFESP] (2011)
Background: Endogenous electric fields and currents occur naturally at wounds and are a strong signal guiding cell migration into the wound to promote healing. Many cells involved in wound healing respond to small physiological electric fields in vitro. It has long been assumed that wound electric fields are produced by passive ion leakage from damaged tissue. Could these fields be actively maintained and regulated as an active wound response? What are the molecular, ionic and cellular mechanisms underlying the wound electric currents?Methodology/Principal Findings: Using rat cornea wounds as a model, we measured the dynamic timecourses of individual ion fluxes with ion-selective probes. We also examined chloride channel expression before and after wounding. After wounding, Ca(2+) efflux increased steadily whereas K(+) showed an initial large efflux which rapidly decreased. Surprisingly, Na(+) flux at wounds was inward. A most significant observation was a persistent large influx of Cl(-), which had a time course similar to the net wound electric currents we have measured previously. Fixation of the tissues abolished ion fluxes. Pharmacological agents which stimulate ion transport significantly increased flux of Cl(-), Na(+) and K(+). Injury to the cornea caused significant changes in distribution and expression of Cl(-) channel CLC2.Conclusions/Significance: These data suggest that the outward electric currents occurring naturally at corneal wounds are carried mainly by a large influx of chloride ions, and in part by effluxes of calcium and potassium ions. Ca(2+) and Cl(-) fluxes appear to be mainly actively regulated, while K(+) flux appears to be largely due to leakage. the dynamic changes of electric currents and specific ion fluxes after wounding suggest that electrical signaling is an active response to injury and offers potential novel approaches to modulate wound healing, for example eye-drops targeting ion transport to aid in the challenging management of non-healing corneal ulcers.